The Impact of Technology-Based Learning Media on the Critical Thinking Skills of 11th-Grade Students at MAN 2 Mojokerto - Widiyaningsih, Puspa Mia; Syafi’i, Muhammad; Rofiqi, Muhammad Abdur (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
Critical thinking is a vital skill for students in the 21st century. The integration of technology into learning plays a crucial role in enhancing the effectiveness and quality of education by providing broader access to information, fostering interactive methods, and supporting the understanding of complex concepts. This study aims to examine the impact of using technology-based learning media on the critical thinking skills of 11th-grade students at MAN 2 Mojokerto. The research is a field study employing a quantitative approach, where data was collected through primary sources and analyzed using simple linear regression to measure how significantly the use of learning media influences students’ critical thinking abilities. The findings show that the use of technology-based learning media has a fairly strong impact, with an effectiveness rate of 76%. Meanwhile, students’ critical thinking skills at MAN 2 Mojokerto are also categorized as fairly good, with a score of 72.5%. In conclusion, the study indicates that technology-based learning media positively influence the critical thinking abilities of 11th-grade students at MAN 2 Mojokerto.